Tracked Changes. Aerospace series. Cable outlet accessories for circular and rectangular electrical and optical connectors. Cable outlet, style K, straight, for heat shrinkable boot, shielded, sealed, self-locking. Product standard Part 064, (26th September 2023) - British Standards Institution,
No abstract available